Emotional Eating and Stress in College Students: A Meta-Analysis Study - Nihayatul Faizah; Eny Purwandari (Research Synergy Foundation, 2025)
This study fills a knowledge gap regarding the relationship between emotional eating and stress in college students, which has not received adequate attention and there have not been many studies that examine the relationship between these two variables in the context of college students. Stress that cannot be managed properly will lead to emotional eating behavior, which, in the future, can have both physical and mental effects on the sufferer; therefore, this research is needed. This study aimed to determine the effect of emotional eating on stress and to detect variations among studies using meta-analysis techniques. This study hypothesizes that there is a significant relationship between emotional eating and stress in university students. This study analyzed 9 primary studies using the keywords